The attributes of ‘Papan Meleh’ - roof eaves decoration in Baitul Rahmah (Kuala Kangsar, Perak, Malaysia) with the historic building information modelling (HBIM) application - Samsudin, Abu Dzar; Zainal Abidin, Norzalifa; Abdullah, Alias; Ali, Maisarah (Malaysian Institute Of Planners, 2020)
Malay building decoration components had been one of the essential elements in Traditional Malay Architecture. This study aims to look in-depth into the process of inputting the attributes data of “Papan Meleh” or roof eaves decoration in Baitul Rahmah building located in Kuala Kangsar using the HBIM application. The method of study for this paper involves three processes, which are the data collection, data process and data fusion. The findings in this study reveal that the data collection from Heritage study report is insufficient in describing the attributes of the roof eaves decoration. The data collection process involves the collection of primary data from the literature review, and secondary data from the heritage report. The secondary data have its limitation in describing the attributes of “Papan Meleh”. Thus, the data process phase is done to correlate the primary and secondary data in finding its generic attributes and remodelling the 2- Dimensional (2D) into 3-Dimensional (3D) model using the HBIM software. The attributes are divided into tangible and intangible data of “Papan Meleh”. After both 3D models of Papan Meleh and its generic attributes are done, both data are fused again through the HBIM software and a complete HBIM model is created.